Cigarette Smoke Exposure Leads to Organic and Mineral Bone Component Changes: The Importance of Rho Kinase Function in These Events - Alex Ferreira da Silva; Franciele Jesus Lima; Alyne Riani Moreira; Cintia do Nascimento Silva; Ivone Braga de Oliveira; Alexandra Fernandes Callera; Ana Luiza Porfirio; Luan Henrique Vasconcelos Alves; Iolanda de Fátima Lopes Calvo Tibério; Ana Paula Pereira Velosa; Vanda Jorgetti; Walcy Rosolia Teodoro; et al. (Cells)
Aberrant Rho-associated kinase function could be associated with increased bone fragility. Since cigarette smoke (CS) exposure promotes the increase in bone fragility due to changes in bone tissue components, this study aimed to investigate how CS exposure could modulate the Rho kinase-associated bone structural changes. Mice were assigned to four groups: control; smoke; control with Rho kinase inhibitor administration; and smoke with a Rho kinase inhibitor. Bone samples were obtained to assess bone histomorphometry analysis, type I collagen composition, and MEPE expression in trabeculae. We observed that CS exposure induced decreased trabecular and osteoid thickness. A concomitant increase in the osteoclastic and erosion surfaces and a decrease in the mineralization surface were observed. Additionally, CS exposure decreased the type I collagen and MEPE expression. Rho kinase inhibitor administration recovered the bone mineralization and the collagen type I deposition. Conclusions: CS exposure increases Rho kinase activity in bone cells, leading to structural changes. The administration of a Rho GTPases inhibitor partially reverses these effects, likely due to the recovery in osteoblast activity.